Solve by using the substitution method $T(n)=T(n-1)+2T(n-2)+3$
Given $T(0)=3$ and $T(1)=5$
I kind of understand it with only one given and one recurrence call by expanding the call using what is inside.
ex. if it was $T(n)=T(n-1)+3$
I would take the $n-1$ and plug it into the the first equation $T(n)=T(n-1)+3$
and repeat until I can find a general case. After that simplify it to get my answer.
My problem is when I have two givens and two recurrences. I first though about solving each one separately using the first recurrence and then the second but it wasn't making any sense to me.